Tracking the Process of a Solvothermal Domino Reaction Leading to a Stable Triheteroarylmethyl Radical: A Combined Crystallographic and Mass‐Spectrometric Study. Issue 12 (21st January 2019) - Liu, Bin; Yu, Fei; Tu, Min; Zhu, Zhong‐Hong; Zhang, Yuexing; Ouyang, Zhong‐Wen; Wang, Zhenxing; Zeng, Ming‐Hua
Abstract: A new free carbon radical was obtained in a microwave‐assisted solvothermal reaction of the primary amine (1‐methyl‐1 H ‐benzo[ d ]imidazol‐2‐yl)methanamine with FeCl3 ⋅6 H2 O in methanol at 140 °C. Through a combination of crystallography and electrospray ionization mass spectrometry, the reaction process was studied. The longest domino reaction includes 14 steps and forms up to 12 new covalent bonds (9 C−N and 3 C−C bonds) and 3 five‐membered heterocycles. For the first time, the homolytic cleavage of a C−O bond was used to synthesize a triarylmethyl radical. Abstract : A free carbon radical was obtained in a domino reaction of a primary amine with FeCl3 ⋅6 H2 O in methanol under solvothermal conditions. In this process, which was studied by crystallography and ESI mass spectrometry, the longest domino reaction features 14 steps, and methanol is sequentially activated; in addition, the homolytic cleavage of a C−O bond is proposed.